Upregulation of mtSSB by interleukin‐6 promotes cell growth through mitochondrial biogenesis‐mediated telomerase activation in colorectal cancer. Issue 10 (6th December 2018) - Wang, Gang; Wang, Qian; Huang, Qichao; Chen, Yibing; Sun, Xiacheng; He, Linjie; Zhan, Lei; Guo, Xu; Yin, Chun; Fang, Yujiang; He, Xianli; Xing, Jinliang
Abstract : It is now widely accepted that mitochondrial biogenesis is inhibited in most cancer cells. Interestingly, one of the possible exceptions is colorectal cancer (CRC), in which the content of mitochondria has been found to be higher than in normal colon mucosa. However, to date, the causes and effects of this phenomenon are still unclear. In the present study, we systematically investigated the functional role of mitochondrial single‐strand DNA binding protein (mtSSB), a key molecule in the regulation of mitochondrial DNA (mtDNA) replication, in the mitochondrial biogenesis and CRC cell growth. Our results demonstrated that mtSSB was frequently upregulated in CRC tissues and that upregulated mtSSB was associated with poor prognosis in CRC patients. Furthermore, overexpression of mtSSB promoted CRC cell growth in vitro by regulating cell proliferation. The in vivo assay confirmed these results, indicating that the forced expression of mtSSB significantly increases the growth capacity of xenograft tumors. Mechanistically, the survival advantage conferred by mtSSB was primarily caused by increased mitochondrial biogenesis and subsequent ROS production, which induced telomerase reverse transcriptase (TERT) expression and telomere elongation via Akt/mTOR pathway in CRC cells. In addition, FOXP1, a member of the forkhead box family, was identified as a new transcription factor for mtSSB. Moreover, our results also demonstrate that proinflammatory IL‐6/STAT3 signaling facilitates mtSSB expression and CRC cell proliferation via inducing FOXP1 expression. Collectively, our findings demonstrate that mtSSB induced by inflammation plays a critical role in the regulation of mitochondrial biogenesis, telomerase activation, and subsequent CRC proliferation, providing a strong evidence for mtSSB as drug target in CRC treatment. Abstract : What's new? Contrary to other cancers, the mitochondrial content in colorectal cancer is frequently increased. Here, the authors point to the tumor inflammatory microenvironment as a critical inducer of mitochondrial biogenesis through increased expression of the mitochondrial single‐strand DNA binding protein (mtSSB). Because this upregulation is ultimately linked to increased cell proliferation, the authors propose that mtSSB‐mediated mitochondrial biogenesis may serve as a new therapeutic target in patients with colorectal cancer.